Measuring the usefulness of information publication time to proxy for returns - Blitzer, Itai (Economics and Business Review, 2015)
This paper deals with investors’ reaction to financial reports submitted by firms to the stock exchange, and specifically measures the influence of publication timing on investors: by using the proximity of the publication date to the regulated publication deadline as an independent variable the study examines whether deadline proximity causes a change in investors’ reaction (as reflected in share returns). Understanding the connection between the publication date and investors’ reaction contributes to the general understanding of financial reports and to the understanding of investors as recipients of those reports. Methodology: quantitative analysis is used based on empirical data collected at the Tel-Aviv Stock Exchange from financial reports published over the fiscal years 2009–2013. The data include quarterly and yearly financial reports and share performance for the corresponding periods. By bundling report publications made within a specific proximity to the deadline and comparing them with investors’ reaction, non-parametric tests reveal a statistically significant correlation between the publication date deadline proximity to the share performance (returns). The conclusion of this research is that the time of financial report publication has an influence on investors’ reaction. This suggests that investors react to financial reports not just based on their intrinsic information content but also in respect of their publication time.